Sales, marketing, continuous improvement : six best practices to achieve revenue growth and increase customer loyalty - Stowell, Daniel M. (San Francisco : Jossey-Bass Publishers, 1997)
Business
Keywords: Selling; Customer; Customer relations; Work groups; Organizational change; Corporate culture